Does the performance of SESDAQ firms improve upon their promotion to the Main Board? - Goh, Hui Ming. (2008)
To determine the probable sources for the positive CARs upon the transition of SESDAQ firms to the Main Board, we examined the trading characteristics of the stocks of the promoted firms as well as the companies’ financial performance. We also examined the extent of the relationship between the relevant factor and the level of CARs.